An analysis of environmental dimensions affected in adoption of hydrogen fuel cell vehicles: A study in Shah ALAM Industrial AREA, Selangor - Siron R.; Lu T.K.; Tasripan M.A. (EDP Sciences, 2023)
Automobiles; Environmental management; Highway engineering; Hydrogen fuels; Environmental information systems; Environmental performance; Environmental risks; Green innovations; Hydrogen fuel cell vehicles; Industrial area; Malaysia; Organizational cultures; Fuel cells